Pelochelys cantorii Gray 1864 - Asian Giant Softshell Turtle - Das, Indraneil (Chelonian Research Foundation, 2008)
The Asian giant softshell turtle, Pelochelys cantorii (Family Trionychidae), is a large freshwater species which can reach 60-100 cm in total carapacen length. It occurs in a variety of habitats, including lakes, rivers, estuaries, seacoasts, and occasionally in coastal marine waters. The species is widespread, occurring from peninsular India to China and Southeast Asia. The taxonomy of the genus Pelochelys has recently been revised, and P.bibroni is now considered to be restricted to southern New Guinea, P.signifera in northern New Guinea, and P. cantorii is now the valid name for the species known from the rest of the range of the genus.